Analisis RC Detector Sebagai Sensor Partial Discharge - Andi Junaidi (KILAT, 2021)
Partial Discharge is a localized electric discharge that only partially connects insulation between conductors, and can appear parallel or not to the conductor. Partial discharge (PD) has long been recognized as an important indication of the state of isolation in high voltage equipment. By measuring PD, a diagnosis of the degree of degradation or deterioration in the isolation conditions of a high voltage device can be determined. Partial Discharge that occurs continuously can cause damage (breakdown) on a high voltage equipment. Therefore, before a high voltage device is used, Partial Discharge detection is necessary. Partial Discharge Detection can use the Partial Discharge measurement circuit. In this study, one part of the Partial Discharge measurement series will be discussed, namely the RC detector. Hopefully, RC detector can be further developed and can be used for more accurate partial discharge detection.